Transcriptomic approach to understanding and characterising disease pathogenesis in sarcoidosis - Kendrick, Y (2017)
Sarcoidosis is a multisystem immunological disorder, centred on the dysregulation of T cell activity, macrophage activation and granuloma formation. Most pulmonary sarcoidosis patients have a good prognosis, but up to 20% can go on to develop lung fibrosis. Previous research in sarcoidosis has generally focused on sarcoidosis as a single disease entity, whereas this thesis has focused on the importance of phenotypical characterisation, in particular active fibrotic pulmonary disease, and the standardisation of measuring disease activity. I first developed a scoring system to measure disease activity based on typical findings on high resolution CT scanning (CTAS). I then identified a set of readily available blood markers and a chest radiographic score as a surrogate for the CT activity score, which enables the physician to easily assess the level of disease activity in the clinic setting (SCAS). Using a transcriptomic approach, I used the activity score to identify the immunological pathways and individual genes correlating directly with increasing activity, both at the site of disease and in the periphery. Enrichment of immune response and defense response gene sets, particularly in BAL cell samples, were observed as disease activity increased, with CCR2, TREM2, and CCL18 featuring as prominent genes involved in the propagation of activity. CXCL9 and CXCL10 were identified as peripheral markers of active disease reflecting the activity in various compartments. In addition, after phenotyping patients with active disease into those with and without fibrosis, differential gene expression showed enrichment of immune related gene sets in the fibrotic cohort, and highlighted the roles of several significantly upregulated genes including CCL19, CCR7, CXCR3, CCR2, ADAMDEC1 and MMP12 in the pathogenesis of fibrotic sarcoidosis. Finally, enrichment of an IPF signature derived from differential expression to sarcoidosis, was observed in the fibrotic sarcoidosis cohort. This information may lend itself to further therapeutic treatments options already used in other fibrotic lung conditions in this interesting and understudied phenotype.